IDENTIFIKASI SURFACE RUBBER COVER UNIT INSERT MACHINE BILLING STATEMENT UNTUK MEMINIMALISIR LAJU KEGAGALAN - Amam Fachrur Rozie; Sumadi Sumadi (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2021)
A rubber cover flyerroll on an insert machine that has been operating for 3600 hours and is damaged, so an analysis is needed to determine the cause of the damage and a process to overcome the damage and the same failure occurs in the future. This flyer roll functions as a billing statement folder before being inserted into an envelope with dimensions of 28 mm (OD) x 284 mm (L). To find out the cause of the damage, several tests were carried out, namely destructive testing and chemical composition testing. Physical tests carried out include hardness test, tensile strength test, modulus test, elongation break test, density test, and abrasion resistance test. resistance test) and in this study a chemical composition test was conducted. From the test results, it can be seen that the hardness value is still within the tolerance limit, which is 94 shore A with a tensile strength value of 31.7 N/mm2 and the results of the chemical composition are dominated by polyurethane rubber at 62.9% and polystar at 23%. So from the tests that have been carried out, it can be concluded that the cause of the damage that occurs to the rubber cover flyer roll is caused by improper maintenance methods, machine maintenance that is not carried out and standard operational procedures (SOPs) that are not carried out according to the recommended maintenance process